Validation of Sharifiella Santos Dias, 1958 (Acari: Ixodidae) as a genus of hard ticks containing S. theilerae (Hoogstraal, 1953), a parasite of tail-less tenrec, Tenrec ecaudatus (Schreber) (Afrosoricida: Tenrecidae) on Madagascar - Apanaskevich, Dmitry A.; Greiman, Stephen E.; Goodman, Steven M.; Apanaskevich, Maria A.; Ahmed, Rokeya; Barker, Stephen C. (Zootaxa, 2025)
We establish Sharifiella Santos Dias, 1958 (Acari: Ixodidae), formerly considered a subgenus of Haemaphysalis Koch, 1844, at full genus rank. The only species of this genus, S. theilerae (Hoogstraal, 1953), is a specific parasite of tenrecs (Afrosoricida: Tenrecidae) on Madagascar. Several morphological characters, including the unique shape of palpal segment II, allow discrimination of this genus and species from any other ixodid ticks. Male, female, nymph, and larva of S. theilerae are redescribed here. Through short-read genomic sequencing we assembled and annotated the entire mitochondrial genome of S. theilerae, as well as assembled the nuclear 28S large ribosomal subunit gene. On the basis of our phylogenies using a nucleotide alignment of the 10 mitochondrial protein-coding genes, as well as the 28S rDNA gene, S. theilerae, is basal to the rhipicephaline lineage (Dermacentor Koch, 1844, Hyalomma Koch, 1844, Rhipicephalus Koch, 1844, and Rhipicentor Nuttall & Warburton, 1908), and not the haemaphysaline lineage.